ANALYSIS THE EFFECT OF COMPENSATION, MOTIVATION, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN CV. CITRA MULYA PERKASA TANGGULANGIN SIDOARJO - Ayu Devy Rustianingtyas; Hermien Tridayanti; Mochammad Arif (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze compensation, motivation, and job satisfaction on CV. Citra Mulya Perkasa. The samples in this study are Owners, General Managers, and employees. Techniques for collecting data on interviews, observation and documentation. This study uses qualitative data analysis which consists of data reduction, presentation of data and conclusions and the validity test of the data, namely triangulation techniques. The conclusion of this study is to provide satisfaction that is rich in assistance and incentives. In addition, employees also expect to be given motivation from the leadership so as to increase the results of employee achievement. Therefore, employees will get satisfaction in working at CV. Citra Mulya Perkasa.